Elevated PSA level as a warning of mesh rejection risk after combined laparoscopic totally extraperitoneal hernia repair and transurethral resection of prostate: Case report - Handaya, Adeodatus Yuda (Int J Surg Case Rep, 2019)
BACKGROUND: Prostate hypertrophy and inguinal hernia are common health issues in men aged more than 50 years. Recently, many studies showed that prostatectomy and laparoscopic inguinal hernia repair could be performed at the same time. This report depicts mesh rejection after concomitant repair of bilateral direct inguinal hernia with TEP and TURP. PRESENTATION OF CASE: A 66-year-old man presented with bilateral direct inguinal hernia and enlargement of the prostate. Prostate biopsy shows atypical adenomatous hyperplasia accompanied by chronic inflammatory cells. Surgery was performed with laparoscopic TEP by using mesh and TURP. The patient underwent a combination of laparoscopic TEP and TURP. A single preoperative and postoperative dose of levofloxacin was administered. The laparoscopic TEP and TURP procedures were completed with no difficulty. Hematoma at the right inguinal occurred three weeks after the procedure. Bilateral inguinal abscess and sepsis occurred at 3-month follow-up. We performed laparotomy mesh evacuation and debridement, and found no recurrence of the hernia. DISCUSSION: Combined laparoscopic TEP hernia repair and TURP are feasible procedures. Bladder erosion caused by mesh might be the cause of mesh infection. However, the elevated PSA levels in this patient can be a warning sign of chronic infection in the prostate which can lead to complications of surgery. CONCLUSIONS: Elevated PSA levels can be a warning before doing a combination of TEP and TURP surgery because they can show signs of infection. However, further research is needed to ascertain the relationship between elevated PSA levels and complications of combination TEP and TURP surgery.